THE TRANSLATION’S TECHNIQUES TO AVOID THE ERROR TRANSLATION OF INDONESIAN TOURIST RESORTS SIGNS INTO ENGLISH - Aprianti, Iis; Siahaan, Desta Gloria; Sulaiman, Eugelin; Pulungan, Anni Holila; Lubis, Syahron (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2022)
This study dealt with the common phenomena error translations in public signs of tourist resorts in Parapat and Bukit Lawang. The objective of this study is to find out the translation’s techniques to avoid error translation of public signs at the two tourist resorts (Parapat and Bukit Lawang). Qualitative research was applied in this study. In process of collecting data, the researcher took supporting instrument, such as camera to catch the photo of public signs in the tourism places in Bukit Lawang-Kabupaten Langkat, and Parapat, Kabupaten Simalungun. The researcher also used English Tourism dictionary as the supporting tools to help the researcher find the natural translation in English translation of public signs in tourism places. The findings of this study showed that there are several techniques can be applied to avoid error translations such as transposition, addition, functional equivalent, cultural equivalent, and naturalization.